Carboranyl Analogues of Celecoxib with Potent Cytostatic Activity against Human Melanoma and Colon Cancer Cell Lines. (23rd January 2019) - Buzharevski, Antonio; Paskas, Svetlana; Sárosi, Menyhárt‐Botond; Laube, Markus; Lönnecke, Peter; Neumann, Wilma; Mijatovic, Sanja; Maksimovic‐Ivanic, Danijela; Pietzsch, Jens; Hey‐Hawkins, Evamarie
Abstract: Nonsteroidal anti‐inflammatory drugs (NSAIDs) are the most common way of treating inflammatory disorders. Their widespread use helped reveal their other modes of action as pharmaceuticals, such as a profound effect on various cancers. Celecoxib has proven to be a very prominent member of this group with cytostatic activities. On the other hand, the highly dynamic field of drug design is constantly searching for new ways of modifying known structures to obtain more powerful and less harmful drugs. A very interesting development is the implementation of carboranes in pharmacologically active structures, mostly as phenyl mimetics. Herein we report the synthesis of three carborane‐containing derivatives of the COX‐2‐selective NSAID celecoxib. The new compounds proved to have promising cytostatic potential against various melanoma and colorectal adenocarcinoma cell lines. Inhibited proliferation accompanied by caspase‐independent apoptotic cell death was found to be the main cause of decreased cell viability upon treatment with the most efficient celecoxib analogue, 3 b (4‐[5‐(1, 7‐dicarba‐ closo ‐dodecaboranyl)‐3‐trifluoromethyl‐1 H ‐pyrazol‐1‐yl]‐1‐methylsulfonylbenzene). Abstract : He said, she said, NSAID : Cyclooxygenase‐2 (COX‐2) plays a prominent role in the occurrence and progression of various cancers. There has been recent expressed focus on the development of new COX‐2‐selective inhibitors as potential cytostatic agents. The highly stable phenyl mimetic carborane was implemented in the structure of celecoxib in order to produce more metabolically stable analogues, and the synthesized compounds were evaluated for their effect on the viability of melanoma and colon cancer cell lines.